Associations between weight gain, integrase inhibitors antiretroviral agents, and gut microbiome in people living with HIV: a cross-sectional study - Julien De Greef; Khoi Nguyen Nguyen; Matthias Van Hul; Anthony Puel; Jean Cyr Yombi; Bernard Vandercam; Anne Vincent; Laure Elens; Leïla Belkhir; Vincent Haufroid; Patrice D. Cani (Scientific Reports)
Abstract Dolutegravir and bictegravir are second-generation HIV integrase strand transfer inhibitors (INSTIs) that were previously associated with abnormal weight gain. This monocentric cross-sectional study investigates associations between weight gain during the first year after initiation of dolutegravir, bictegravir or other anchor drugs and gut microbiome diversity as well as taxa composition. The study enrolled 79 participants receiving dolutegravir, 32 receiving bictegravir and 10 receiving non-INSTI based regimens. Most of them were treatment experienced at initiation of those anchor drugs agents. Although weight gain was not linked to overall bacterial diversity, strong associations with specific taxa were demonstrated (FDR q < 0.01). Using multiple linear regression, we identified 4 distinct groups of bacteria associated with either dolutegravir, bictegravir, weight loss or weight gain under treatment, allowing a machine learning model to predict 15.9% of the weight gain variability regardless of sex, age and body mass index (RMSE: 0.0126). Dysosmobacter sp. and Haemophilus sp., two bacteria previously associated with host metabolism, were among the strongest predictors. Our findings link INSTIs, weight gain, and the gut microbiome. Future research should investigate the causal role of the identified taxa to improve our understanding of microbiome-drug interactions and further support personalized antiretroviral strategies. Trial registration: Eudra-CT 2020-001103-17 (registration date: 2020–12-01).